1983
DOI: 10.7164/antibiotics.36.1078
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of kijanimicin.

Abstract: Kijanimicin is a novel tetronic acid structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Most members of this group show potent activity against Gram-positive bacteria 34e , 36 as well as cytotoxicity against various cancer cell lines. 36a , 36b , 37 In addition, kijanimicin was shown to exhibit robust anticancer 38 and antimalarial activities 34e in mouse models. Moreover, Fenical et al reported promising anti-inflammatory activities of lobophorins in a mouse ear edema model.…”
Section: Biology Of Spirotetronate Polyketidesmentioning
confidence: 99%
“…Most members of this group show potent activity against Gram-positive bacteria 34e , 36 as well as cytotoxicity against various cancer cell lines. 36a , 36b , 37 In addition, kijanimicin was shown to exhibit robust anticancer 38 and antimalarial activities 34e in mouse models. Moreover, Fenical et al reported promising anti-inflammatory activities of lobophorins in a mouse ear edema model.…”
Section: Biology Of Spirotetronate Polyketidesmentioning
confidence: 99%
“…Versipelostatin, also derived from Streptomyces sp., also has a structure very similar to the lobophorins and has been reported to activate the UPR. 16,17 Although antimicrobial and antitumor activities have been reported for kijanimicin 18 and lobophorins, 13,19−23 herein we report the ability of lobophorins A, B, E, F, and CR1 (1−5) to activate the UPR and cell death in two human oral squamous cell carcinoma (OSCC) cell lines.…”
mentioning
confidence: 78%
“…Unfortunately, the limited cultivability of these lobophorins prevented the evaluation of lobophorins CR2 and CR3 [96]. Lobophorin B ( 58 ) is nearly identical to kijanimicin ( 59 ) [60,98], lacking an additional glycosylation at the B-sugar. Lobophorins CR2 and CR3 ( 60 , 61 ) appear to be allylic oxidation products of 58 , suggesting a biosynthetic relationship that merits further exploration.…”
Section: Class II Marine Spirotetronatesmentioning
confidence: 99%